PERBEDAAN INDEKS HIGIENE ORAL DAN pH PLAK KELOMPOK PEMAKAI DAN BUKAN PEMAKAI PESAWAT ORTODONTI CEKAT - Vika Oktaviani; Oedijani Santoso (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2016)
Background: Orthodontic treatment can have an impact in the form of changes in the oral environment and the composition of the oral flora, causing changes the amount and pH of plaque that can cause dental caries and gingivitis.Aim: To determine the difference on oral hygiene index and pH of plaque group of users and non users of fixed orthodontic appliances.Methods: This research is analytical observational research by using cross sectional design. The subjects of the research were as many as 54 students who were divided into group of the users and group of the non users fixed orthodontic appliances. This research began with the measurement of the pH of plaque by using pH meter, then assessment of Oral Hygiene Index which obtained by summing the scores of debris and scores of calculus of each student.Results: The result of the research with statistical test that there was increase on oral hygiene index in the group of users (0,45 ± 0,250) and non users of fixed orthodontic appliances (0,38 ± 0,217). pH of plaque in the group of users fixed orthodontic appliances lower (0,38 ± 0,217) than group of non users of fixed orthodontic appliances (7,18 ± 0,131).Conclusion: There was no significant difference about Oral Hygiene Index Simplified (OHI-S) in the group of users and group of the non users fixed orthodontic appliances and there was significant difference between the pH of plaque in the group of users and group of the non users fixed orthodontic appliances.